2020
DOI: 10.1016/j.brachy.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of prostate brachytherapy techniques with polyethylene glycol–based hydrogel spacers: A systematic review

Abstract: The objective of this overview was to critically evaluate the effect of polyethylene glycol (PEG)-based hydrogel spacers during prostate brachytherapy with regard to dosimetric and clinical benefits, as well as procedure-related toxicity. METHODS AND MATERIALS: A systematic search in the PubMed database was performed. RESULTS: A total of 12 studies, involving 615 patients with PEG hydrogel injection, were included. Overall, patients well tolerated the implantation of PEG hydrogel spacers with an excellent safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Several systematic reviews have provided qualitative evaluations of different perirectal spacer materials delivered prior to prostate RT, [5][6][7] yet quantitative synthesis of clinical results with specific spacers is limited, to our knowledge. One method to reduce rectal toxic effects involves an absorbable polyethylene glycol hydrogel spacer (SpaceOAR; Boston Scientific), which is injected between the Denonvilliers fascia and anterior rectal wall prior to RT.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have provided qualitative evaluations of different perirectal spacer materials delivered prior to prostate RT, [5][6][7] yet quantitative synthesis of clinical results with specific spacers is limited, to our knowledge. One method to reduce rectal toxic effects involves an absorbable polyethylene glycol hydrogel spacer (SpaceOAR; Boston Scientific), which is injected between the Denonvilliers fascia and anterior rectal wall prior to RT.…”
Section: Introductionmentioning
confidence: 99%
“…С учетом последних тенденций по локальной эскалации дозы под этот критерий попадает подавляющее большинство клинических сценариев радиотерапии РПЖ (конформная ДЛТ в режиме стандартного фракционирования и умеренного гипофракционирования, стереотаксическая лучевая терапия (СТЛТ), протонная лучевая терапия, высоко-и низкомощностная брахитерапия). В настоящее время опубликованы данные, свидетельствующие о преимуществах промежностного введения БДС при всех современных технологиях облучения ПЖ [23,[31][32][33][34].…”
Section: методика применения спейсеров и их характеристикаunclassified
“…It has been shown that rectal spacer devices (endorectal balloons, biodegradable balloons or hydrogel spacers) can help stabilise the prostate during local therapy, by increasing the space between Denonvillier's fascia and the rectal wall, thereby decreasing radiation exposure 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…SpaceOAR hydrogel is the most widely studied rectal spacer, which maintains a stable separation between the prostate and rectum for up to 12 weeks, before hydrolysis, absorption and renal excretion 13‐15 . In the prospective pivotal phase III study, 222 patients with T1‐2 prostate cancer were randomised to SpaceOAR or no spacer during treatment with IMRT; there was a 74% reduction in rectal radiation dose 15 .…”
Section: Introductionmentioning
confidence: 99%